The structural relationship among students’ perceptions of sales-related skills, sales careers, and views of others and the intention to pursue sales careers in Malaysia: the mediating effect of feelings towards selling - Nor Asiah Omar,; Nadzirah Rosli,; Syed Shah Alam,; Abu Hanifah Ayob,; Muhamad Azrin Nazri, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Companies are increasingly looking for sales professionals. However, most university students are hesitant to consider sales as a prospective job option after graduation. Understanding the determining factors that influence graduates’ willingness to work in sales in Malaysia is critical in persuading more students to engage in sales career and restoring market demand for sales employment. Thus, this study investigates the relationship between perceptions of sales-related skills, perceptions of sales careers, and perceptions of how others view salespeople and the intention to pursue sales career among students in Malaysia’s universities. The effect of feelings towards selling as a mediator is also explored. The study analyses data from 276 business undergraduates using a structural equation modeling approach. The research findings indicate that perceptions of sales-related skills, perceptions of sales careers, and perceptions of how others view salespeople have positive impacts on intention to pursue sales career. There was also evidence that shows feelings towards selling influence intention to pursue sales career directly and indirectly. This study adds to the body of knowledge regarding sales education and provides universities practical insights into the factors determining student intentions to pursue sales jobs.